-9x+4X-3+7=

Simple and best practice solution for -9x+4X-3+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+4X-3+7= equation:


Simplifying
-9x + 4X + -3 + 7 = 0

Reorder the terms:
-3 + 7 + 4X + -9x = 0

Combine like terms: -3 + 7 = 4
4 + 4X + -9x = 0

Solving
4 + 4X + -9x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + 4X + -4 + -9x = 0 + -4

Reorder the terms:
4 + -4 + 4X + -9x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 4X + -9x = 0 + -4
4X + -9x = 0 + -4

Combine like terms: 0 + -4 = -4
4X + -9x = -4

Add '9x' to each side of the equation.
4X + -9x + 9x = -4 + 9x

Combine like terms: -9x + 9x = 0
4X + 0 = -4 + 9x
4X = -4 + 9x

Divide each side by '4'.
X = -1 + 2.25x

Simplifying
X = -1 + 2.25x

See similar equations:

| x+.22x=5000 | | 8+5x^2=-3x | | y=-x^2+5x+8 | | 260=10q+n | | 3x+6=2x+17 | | 3k-7=21 | | 4v-7=13 | | 12x-9=8x+27 | | 2.5x=5x | | 7-8x=3x+15 | | sqrt(3x+1)-2=6 | | 2(3x-4)=#x+1 | | 2x+22=4x | | (120-85)=x | | 8x-8=8x-1 | | 20-g=-19+2g | | 45x=9x^2 | | 0=-10y-2x | | x/507+6-6=715 | | -16x^2+68x+4=20 | | 20-12n+20=-20-2n | | -x^2+15x-56=0 | | 3b+2a=22 | | 5Y-65Y=200 | | 20b+16= | | -9b+16=-11b | | 5y^3(5y^2-7y+9)= | | 4+.20P=5+30P | | YZ=0 | | .66+.75x=.83 | | 3y-x-3=0 | | y=4x^2+32x+61 |

Equations solver categories